EFFECT OF DIETARY SUPPLEMENTATION OF PREBIOTIC, ANTIBIOTIC AND HERBAL COMPOUNDS ON GROWTH, FEED INTAKE AND FCR IN NEW ZEALAND WHITE RABBITS - Shaik Khadeer Basha; L.S.S. Varaprasad Reddy; A.V.N. Sivakumar; D. Suresh Babu; B.R. Naik; M. Kalyana Chakravarthi (Indian Journal of Veterinary and Animal Sciences Research, 2025)
The present study was conducted on one month age twenty four weaned broiler rabbits having similar body weights, which were divided into four groups with 6 rabbits in each group for a period of 42 days to study the effect of inclusion of Mannan oli gosaccharides (MOS), Oxytetracycline and Ocimum sanctum supplements in the basal diet on growth performance, feed intake and FCR in New Zealand white rabbits. The study revealed that initial and final body weights, daily and weekly feed intakes and FCR did not differ significantly. However, higher body weights and lower FCR values were recorded in treatment groups supplemented with MOS and Tulasi (Ocimum sanctum).